Recurrent Vestibular Symptoms Not Otherwise Specified: Clinical Characteristics Compared With Vestibular Migraine and Menière's Disease - Dlugaiczyk, Julia; Lempert, Thomas; Lopez-Escamez, Jose Antonio; Teggi, Roberto; von Brevern, Michael; Bisdorff, Alexandre (Frontiers in Neurology, 2021)
Despite the huge progress in the definition and classification of vestibular disorders within the last decade, there are still patients whose recurrent vestibular symptoms cannot be attributed to any of the recognized episodic vestibular syndromes, such as Menière's disease (MD), vestibular migraine (VM), benign paroxysmal positional vertigo (BPPV), vestibular paroxysmia, orthostatic vertigo or transient ischemic attack (TIA). The aim of the present multi-center, cross-sectional study was to systematically characterize the clinical picture of recurrent vestibular symptoms not otherwise specified (RVS-NOS) and to compare it to MD and VM. Thirty-five patients with RVS-NOS, 150 patients with VM or probable VM and 119 patients with MD were included in the study. The symptoms of RVS-NOS had been present for 5.4 years on average before inclusion, similar to VM and MD in this study, suggesting that RVS-NOS is not a transitory state before converting into another diagnosis. Overall, the profile of RVS-NOS vestibular symptoms was more similar to VM than MD. However, in contrast to VM, no female preponderance was observed for RVS-NOS. Positional, head-motion and orthostatic vertigo were reported more frequently by patients with RVS-NOS than MD, while external vertigo was more prevalent in the MD group. At group level, the spectrum of attack durations from minutes to 3 days was evenly distributed for VM, while a small peak for short and long attacks in RVS-NOS and a big single peak of hours in MD were discernible. In general, vertigo attacks and associated vegetative symptoms (nausea and vomiting) were milder in RVS-NOS than in the other two disorders. Some patients with RVS-NOS described accompanying auditory symptoms (tinnitus: 3%, aural fullness and hearing loss: 6% each), migrainous symptoms (photophobia, phonophobia or visual aura in 6% each) or non-migrainous headaches (14%). These findings suggest that RVS-NOS is a stable diagnosis over time whose overall clinical presentation is more similar to VM than to MD. It is more likely to be composed of several disorders including a spectrum of mild variants of known vestibular disorders, such as VM and MD, than a single disease entity with distinct pathognomonic features.